(untitled) (قضايا سياسية, 2025)
This research was prepared by (Mostafa Al-Nashar), the Egyptian researcher and professor of philosophy at the Faculty of Arts, Cairo University. He specializes in studies of ancient Greek and Eastern thought and has several studies and research works, including "The History of Greek Philosophy" in several volumes, and "Post-Globalization: A Reading of the Future of Civilizational Interaction," among many others. This research contribution is part of extensive critical studies of Western centrality, aiming to shed light on the deeply rooted racist tendencies within Western nations and the political thought of its most important philosophers and thinkers regarding other nations and peoples.